The boob diaries: Discourses of breastfeeding in 'exclusive pumping' blogs. (December 2020) - Coffey-Glover, Laura
Abstract: This paper uses a feminist discourse analytical approach (Sunderland 2000, 2004; Lazar 2005, 2007 ) to analyse a set of online blogposts and personal webpages from 'exclusive pumpers' (EPers): women who express breastmilk as an alternative to breastfeeding and using infant formula. Using tools from evaluation and stance analysis (Hunston and Thompson, 2000; Bednarek 2006; Myers 2010 ), I examine how EPers construct opinions about exclusive pumping and breastfeeding. The analysis is centred around three interrelated discourses of exclusive pumping (that are both positively and negatively valued): (1) exclusive pumping as equivalent to breastfeeding; (2) exclusive pumping as a challenge; (3) exclusive pumping as mitigating a failure to breastfeed. This nexus of discourses can be viewed as being underpinned by an 'overarching' discourse (Sunderland 2000 ) of 'exclusive pumping as abnormal'. The implications of this hegemonic, overarching discourse are discussed in relation to a constructed dichotomy of 'breastfeeding' versus 'bottle feeding'. I show how this dichotomy, and the hegemonic discourse of 'EPing as abnormal'/'breast is best' serves to (re)produce discourses of normative motherhood.